ANALISIS FAKTOR YANG MEMPENGARUHI PEMBERIAN AIR SUSU IBU (ASI) EKSKLUSIF DI WILAYAH KERJA PUSKESMAS CILACAP TENGAH I KABUPATEN CILACAP TAHUN 2017 - ., Sohimah; Lestari, Yogi Andhi (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
Exclusive Breastfeeding (ASI) is a living liquid that can adjust the content of substance that can meet the nutritional needs of infants (Maryunani 2012, 40). Based Riset Kesehatan Dasar (Riskesdas) of 2013 infants exclusively breastfeeding for six months is only 40.6%, far from the national target of 80%. The problems in the practice of exclusive breastfeeding is the social and cultural factors of economic (family support, education, income and employment status mothers), factors maternal age (readiness mothers in breastfeeding), factor parity mother, a factor of support from family, factor a lack of staff health and support community health workers making less light or encouragement about the benefits of exclusive breastfeeding. Purpose of the Research Purpose of the research to knowing the analysis of factors that influencing exclusive breastfeeding. Methods of the Research The research is an explanatory research using cross sectional method. Subject Research This is the infant more 6 months and less of 12 months. Sample selection techniques that will be used in this research is cluster sampling. Analysis of the data in this research used Chi Square and Logisticregression. Result of the Reasearh: results of the research that factors influencing to exclusive breastfeeding is factor age (p value 0.012 <0.05), knowledge (p value 0.003> 0.05) and support family (p value 0.000> 0.05). The most influential factor to exclusive breastfeeding is support family. Conclusion: A Significant influence factor age,knowledge and support family factor to exclusive breastfeeding. Key Word: exlusive breastfeeding, occupation,education,age of mother, parity, support family